Fisherman with Disabilities from Batu Karas - Risky Noer Safitri; dwi Anggyan; seno maulana; Firgiawan Firgiawan; Hanif Marwan Hakim; Nur Fauzan (Universitas Pendidikan Indonesia, 2021)
Marine resources in the fisheries sector of Batu Karas Beach are one of the main sectors of the community's economy. A total of 362 residents work as traditional fishermen there. In reality, being a fisherman is a job that has a high risk, because it is very dependent on nature, especially when the weather changes are sometimes extreme, so body stability is very necessary. However, it turns out that not all fishermen are physically perfect, there is a fisherman from Batu Karas named Uus usmawan who has physical limitations, but must continue to go to sea because he is the backbone of his family. The purpose of this study is to see how a person with a disability who works as a fisherman navigates his life, sea, boat, family and social environment. This research uses descriptive analysis method through observation, interview, documentation study and literature study. Research data obtained as the main data in making a documentary. The results of this study indicate that a person with a disability needs to be mentally and physically strong to work as a fisherman. So that government intervention is very important to give special attention to programs and special treatment as well. The implication of this research is as an illustration for the government to find solutions for the disabled fisherman profession.